Электроэнергетическая система на возобновляемых источниках энергии - Лукутин Б. В. Борис Владимирович; Обухов С. Г. Сергей Геннадьевич; Плотников И. А. Игорь Александрович; Шандарова Е. Б. Елена Борисовна
опубл. 27.02.13